Antioxidant effect of aqueous extract of four plants with therapeutic potential on gynecological diseases; Semen persicae, Leonurus cardiaca, Hedyotis diffusa, and Curcuma zedoaria. Issue 1 (December 2017) - Ji, Shaojian; Fattahi, Amir; Raffel, Nathalie; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf; Schrauder, Michael
Abstract Background Little information is available concerning antioxidant effects of plant teas (water boiled) which are used more commonly in traditional Chinese medicine than other extracts. Thus, we addressed this issue by evaluating the ability of teas from four different plants with therapeutic potential on gynecological diseases. Methods The aqueous extracts ofSemen persicae, Leonurus cardiaca, Hedyotis diffusa, andCurcuma zedoaria rhizome were prepared and then their effects on copper-induced low-density lipoprotein cholesterol (LDL-C) oxidation were evaluated by spectrophotometric method. Density gradient ultracentrifugation method was recruited to isolate LDL-C from healthy individuals. Results Our results showed that adding 10, 20, and 30 µlS. persicae could increase the lag phase duration of LDL-C oxidation compared with control reaction 12, 21, and 33%, respectively. The most effective delay (87%) was observed when 30 µlH. diffusa was added to the reaction. In cases ofL. cardiaca andC. zedoaria, we found no significant influence on the lag phase duration (p > 0.05). Moreover, our findings about starting point of the decomposition phase were almost in parallel with the lag phase results, as 30 µl ofS. persicae orH. diffusa teas could significantly increase the initiation time of decomposition (p < 0.05). Conclusions In conclusion our results showed that bothS. persicae andH. di ffusa teas and notL. cardiaca andC. zedoaria could have medicinal therapeutic effects partly through direct oxidation prevention.